Proceedings of the Second International Symposium on Radiation Detectors and Their Uses (ISRD2018) 2019
DOI: 10.7566/jpscp.24.011016
|View full text |Cite
|
Sign up to set email alerts
|

4π Compton Gamma Imaging toward Determination of Radioactivity

Abstract: For rapid detection and characterization of radioactive materials in rather large area, we have developed a portable 4π sensitive γ-ray imager based on Compton imaging. Using a prototype based on a 3D pixel array CdTe detector, radioactive source positions such as 137 Cs and natural uranium metal sample were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The energy deposited on each pixel because of the incident gamma rays was recorded as listmode data. The basic performance of the detector as the 4π gamma imager was reported in our previous papers [10,11].…”
Section: Verification Based On the Integrated Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy deposited on each pixel because of the incident gamma rays was recorded as listmode data. The basic performance of the detector as the 4π gamma imager was reported in our previous papers [10,11].…”
Section: Verification Based On the Integrated Simulation Modelmentioning
confidence: 99%
“…Hence, 4π Compton imaging can allow more rapid identification of radiation sources than that possible by methods based on conventional gamma imaging. In this regard, we developed a 4π gamma-ray imaging system using gadolinium aluminum gallium garnet (GAGG) scintillators [8,9] and CdTe detectors [10,11]. Previous studies demonstrated that the location and activity of hidden gamma-ray sources can be estimated by combining gamma-ray images measured at multiple positions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1(a) shows the schematic of the 4π gamma imager used in this study. 7,8) For 4π gamma imaging, a detector provides a three-dimensional position and the deposited energy at an interaction point should be used. Here, coincidence events where a photoelectric absorption occurs after a Compton scattering of the incident gamma ray in the detector are used for 4π gamma imaging.…”
Section: Principle and Reconstruction Of 4π Gamma Imaging On The Spherementioning
confidence: 99%
“…6) A typical Compton imager has a maximum field of view of 180°; however, in cases where the direction of the incident gamma rays cannot be specified in advance or where gammarays enter the imager from all directions, it is desirable to have sensitivity in all directions to the imager. Therefore, we have developed a 4π direction-sensitive-gamma imaging method (4π gamma imaging) 7,8) based on the principle of Compton imaging. As 4π gamma imaging can measure the direction and flux of incident gamma rays from all directions, we have applied it to develop a method for finding unknown radiation sources.…”
Section: Introductionmentioning
confidence: 99%
“…33) Compton cameras and active coded-mask cameras have been enhanced to cover a full 4π FOV. [34][35][36][37][38][39][40][41][42][43][44] We introduce a novel gamma-ray imaging approach. The proposed method uses multiple shielding cubes randomly spread in three-dimensional (3D) space to create unique gammaray flux patterns.…”
Section: Introductionmentioning
confidence: 99%